#TITLE_ALTERNATIVE# - PARAMITHA (NIM : 10108034); Pembimbing : Dr. Leo H. Wiryanto, CYNTHIA
A fluid flows on the channel with a barrier which causes the emergence of a jet. The stream can be represented by a complex potential f(z) = φ(x, y) + iψ(x, y), with respect to the fluid domain z = x + iy. Some examples of complex potential for simple flow is given. Analysis of the complex potential function near the separation point performed to get the local flow behavior as it leave the solid boundary. This result is useful in determining the design of discretisation in numerical prosedure.